2015
DOI: 10.1055/s-0034-1380518
|View full text |Cite
|
Sign up to set email alerts
|

N-Bromosuccinimide as a Brominating Agent for the Transformation of N-H (or N-Benzyl) Ketoaziridines into Oxazoles

Abstract: A novel procedure for the direct synthesis of 2,5-diaryloxazoles starting from N-H ketoaziridines is described. The method proceeds via the in situ formation of N-bromoketoaziridines in the presence of N-bromosuccinimide followed by the generation of intermediate azomethine ylides. A plausible mechanism for this transformation is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Apart from N ‐bromosuccinimide (NBS), which is the most commonly used NBr reagent in organic synthesis, several other NBr reagents that act as electrophilic bromine(I) reagents are known, including the commercially available bis(2,4,6‐trimethylpyridine)bromine(I) hexafluorophosphate, in which a bromonium ion is coordinated with two pyridine units . However, an array of versatile reactions with NBS, spanning the areas of oxidations, rearrangements, and C–H functionalizations, are well known, owing to its ease of availability, economical pricing, and ease of handling (Figure ) , …”
Section: Classical Use Of Halonium Ions and Commercially Availablementioning
confidence: 99%
“…Apart from N ‐bromosuccinimide (NBS), which is the most commonly used NBr reagent in organic synthesis, several other NBr reagents that act as electrophilic bromine(I) reagents are known, including the commercially available bis(2,4,6‐trimethylpyridine)bromine(I) hexafluorophosphate, in which a bromonium ion is coordinated with two pyridine units . However, an array of versatile reactions with NBS, spanning the areas of oxidations, rearrangements, and C–H functionalizations, are well known, owing to its ease of availability, economical pricing, and ease of handling (Figure ) , …”
Section: Classical Use Of Halonium Ions and Commercially Availablementioning
confidence: 99%
“…91 Under thermal conditions, N-bromo substituted ketoaziridines 173 are converted into an azomethine ylide 175 via C-C bond cleavage that is followed by the ring-closure of the latter leading to a cyclized intermediate 176, which then undergoes thermal elimination of hydrogen bromide to produce oxazoles 174 (Scheme 52). The authors have also reported that the presence of electron-withdrawing R 1 groups and electron-donating R 2 groups favored the formation of azomethine ylide.…”
Section: Synthesis Of Oxazolesmentioning
confidence: 99%
“…10 N-Bromosuccinimide was reported to successfully promote this transformation in refluxing dioxane. 12 Bromination of the unsubstituted nitrogen atom was assumed to facilitate thermal C-C bond cleavage of the aziridine ring and this effect was also demonstrated for 2benzoyl-1-benzyl-3-phenylaziridine. Heating this aziridine in dioxane afforded only 17% yield of 2,5-diphenyloxazole while addition of NBS increased it to 87%.…”
Section: Short Review Syn Thesismentioning
confidence: 98%